Direct Observation of Large Deformation and Fracture Behavior at the Crack Tip of Slide-Ring Gel. Issue 9 (1st January 2019) - Liu, Chang; Mayumi, Koichi; Hayashi, Kyohei; Jiang, Lan; Yokoyama, Hideaki; Ito, Kohzo
Abstract : Slide-ring gel is a highly deformable polymer gel prepared by cross-linking rings on polyrotaxanes, in which ring molecules are threaded onto a linear polymer chain. The remarkable extensibility of SR gels is due to the stress equalization effect caused by the sliding of cross-links on polymer chains. We directly observed the stress equalization effect by magnifying the instinctive micron-scale defect to artificial millimeter-scale crack and then mapping the crack tip stress field based on photoelasticity. By reducing coverage of rings on polymer chains in SR gels, obvious crack blunting and delayed crack growth are observed. Highly elongated non-linear "cohesive zone" with length of 0.6 mm and width less than 0.1 mm occurs ahead of crack tip before crack propagation. Our results show that SR gels with low ring coverage have large cohesive strength to survive large deformation before elastic chains rupture, which is essentially derived from the sliding of the cross-links that adjusts strand length automatically to equalize stress in the network.